2017
DOI: 10.1016/j.metabol.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the management of hyperglycaemic emergencies in adults with diabetes

Abstract: Hyperglycaemic emergencies are associated with significant morbi-mortality and healthcare costs. Management consists on fluid replacement, insulin therapy, and electrolyte correction. However, some areas of patient management remain debatable. In patients without respiratory failure or haemodynamic instability, arterial and venous pH and bicarbonate measurements are comparable. Fluid choice varies upon replenishment phase and patient's condition. If patient is severely hypovolaemic, normal saline solution shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 72 publications
0
10
0
2
Order By: Relevance
“…While there may be some indication for its use in severe DKA with pH <6.9, there have been no prospective randomised studies to support this approach. There are also concerns that bicarbonate replacement may be associated with hypokalaemia, central nervous system acidosis and cerebral oedema …”
Section: Discussionmentioning
confidence: 99%
“…While there may be some indication for its use in severe DKA with pH <6.9, there have been no prospective randomised studies to support this approach. There are also concerns that bicarbonate replacement may be associated with hypokalaemia, central nervous system acidosis and cerebral oedema …”
Section: Discussionmentioning
confidence: 99%
“…However, this rate has not been proven to be sufficient to suppress lipolysis and ketosis 72. Additional studies are needed to assess whether the potential benefits of reduction of the insulin rate (reduced hypoglycemia and hypokalemia) justify the potential delay in resolution of diabetic ketoacidosis.…”
Section: Acute Managementmentioning
confidence: 99%
“…On the other hand, some authors have reported higher rates of mortality: 17.14% in South Africa in 2017 [23]; 27.5% in the Democratic Republic of Congo in 2014 [6]; 40.5% in Mali in 2007 [24] and 48.7% in Burkina Faso in 2017 [1]. In the northern countries, the death rates are rather lower: less than 1% in the USA in 2017 and 2016 [25,26]; 1.2% in Spain in 2015 [27]; 1.7% in China in 2016 [28]. In addition, taking into account the publication dates of the various studies, there is a decrease in mortality rates in the most recent studies and certainly because of therapeutic progress and improvements in technical facilities.…”
Section: Discussionmentioning
confidence: 99%